2018
DOI: 10.1590/1518-8345.2110.3035
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding self-efficacy and postpartum depression: a cohort study

Abstract: Objective:to evaluate breastfeeding self-efficacy, the presence of postpartum depression symptons and the association between breastfeeding self-efficacy and postpartum depression with cessation of exclusive breastfeeding. Method:cohort study with 83 women. The instruments used were the Breastfeeding Self-Efficacy Scale and the Edinburgh Postnatal Depression Scale. Statistical analysis was conducted using the log-rank tests, analysis of variance and the Cox survival model. Results:breastfeeding self-efficacy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
25

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 25 publications
4
31
0
25
Order By: Relevance
“…We found that antenatal well-being and PPD were associated with any breastfeeding but not with exclusive breastfeeding. Others have observed that women with depressive symptoms exclusively breastfed less frequently [58]. Current research expands our findings, reporting inverse associations between antenatal depressive symptoms and the initiation of breastfeeding as well as observations that both antenatal depression and PPD predict early cessation of breastfeeding [57,59,60].…”
Section: Discussionsupporting
confidence: 84%
“…We found that antenatal well-being and PPD were associated with any breastfeeding but not with exclusive breastfeeding. Others have observed that women with depressive symptoms exclusively breastfed less frequently [58]. Current research expands our findings, reporting inverse associations between antenatal depressive symptoms and the initiation of breastfeeding as well as observations that both antenatal depression and PPD predict early cessation of breastfeeding [57,59,60].…”
Section: Discussionsupporting
confidence: 84%
“…Banyak faktor ibu tidak memberikan ASI secara eksklusif seperti usia ibu yang terlalu muda, pendidikan yang rendah, merokok dan lain sebagainya. Tetapi dengan ibu terus menerus menyusui pada 6 bulan pertama kelahiran akan mengurangi tingkat terjadinya depresi dini postpartum (Vieira et al, 2018).…”
Section: Tidak Asi Eksklusifunclassified
“…On the other hand, a study from Turkey found mode of delivery to have no significant impact on the development of postnatal depression [ 23 ]. Studies have also tried to link PPD with breastfeeding [ 24 – 26 ], although methodological flaws made it difficult to draw conclusions [ 27 ]. All these findings call for systematic assessment of presumed potential predictors of PPD.…”
Section: Introductionmentioning
confidence: 99%